2019
DOI: 10.1007/s11469-018-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Sports Betting into a Rapid and Continuous Gambling Activity: a Grounded Theoretical Investigation of Problem Sports Betting in Online Settings

Abstract: There is an increasing trend for online sports betting to be identified in gambling treatment services as the principal gambling activity that leads to harmful consequences. The structure of sports betting in online settings has changed extensively in the last 5 years in response to developing information technology, and these changes appear to have increased the inherent risk associated with online sports betting. There is a current need to understand disordered patterns of sports betting in online settings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 39 publications
3
42
0
1
Order By: Relevance
“…The results demonstrated that sports bettors with high problem gambling scores were more likely to use in-play betting and the ‘cash out’ feature. More recently, Parke and Parke ( 2019 ) carried out in-depth interviews with 19 online problem gamblers. The core theme to emerge was labelled the ‘online sports betting loop’, which comprised the new structural features of the online sports betting market, and included in-play sports betting, cash out, and instant depositing.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that sports bettors with high problem gambling scores were more likely to use in-play betting and the ‘cash out’ feature. More recently, Parke and Parke ( 2019 ) carried out in-depth interviews with 19 online problem gamblers. The core theme to emerge was labelled the ‘online sports betting loop’, which comprised the new structural features of the online sports betting market, and included in-play sports betting, cash out, and instant depositing.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, those with a gambling problem bet more heavily in-play compared to before games commenced. Analysis of customer account data from a small sample of individuals classified as having gambling problems found that live betting increased betting opportunities and motivated loss chasing, resulting in persistent and extended betting sessions (28). In-play betting created fewer natural breaks in play due to short periods between a bet being placed and the outcome being determined, thus reducing the opportunity for reductions in arousal and other emotional responses stimulated by betting, winning, and losing.…”
Section: The Association Between Online In-play Betting and Problem Gmentioning
confidence: 99%
“…In a survey of online sports bettors, gamblers felt that online betting is riskier than in-venue sports betting because of the features of online gambling websites (Parke & Parke, 2019). For example, those surveyed indicated that being able to deposit money instantly into an online account makes it more likely an individual will chase their losses and less likely that individual will take a break from play (Parke & Parke, 2019). Unfortunately, bettors who have gamblingrelated problems might be more likely to use these novel internet sports betting options.…”
Section: Internet Sports Bettingmentioning
confidence: 99%